Rare earth elements recovery from end-of-life NdFeB magnets towards new applications using design of experiments for leaching process - Ana Paula Silva; Óscar Barros; Pier Parpot; Isabel C. Neves; Teresa Tavares; José Pinheiro-Torres; Bruna Silva (Minerals Engineering, 2026)

Highly efficient (MFe)zeolite catalysts for nimesulide degradation via Fenton-type oxidation - Carmen S.D. Rodrigues; Susana Costa; Olívia S.G.P. Soares; António M. Fonseca; Pier Parpot; Manuel F.R. Pereira; Luis M. Madeira; Elisabetta Rombi; Isabel C. Neves (Chemical Engineering Journal, 2026)

Iron-exchanged Y-type zeolites for phosphorus recovery from eutrophic waters: Kinetics and performance in real lake matrix - Anna C.M. Martins; Jéssica T. Santos; Teresa Tavares; António G. Brito; António M. Fonseca; Isabel C. Neves; Gilberto Martins (Journal of Environmental Chemical Engineering, 2026)

Immobilization of laccase on grape seed-derived hydrochar and biochar as sustainable biocatalysts for efficient pharmaceutical degradation in real wastewater - Helena Sá; Michele Michelin; Teresa Tavares; Maria Angeles Sanroman; Emilio Rosales; Isabel C. Neves; Bruna Silva (Journal of Environmental Chemical Engineering, 2025)

Bimetallic-zeolite nanomaterials as catalysts for degradation of azorubine dye via Fenton-like oxidation - Imane El Mrabet; Bebiana L.C. Santos; Karim Tanji; Elisabetta Rombi; Pier Parpot; António M. Fonseca; Hicham Zaitan; Isabel C. Neves (Journal of Water Process Engineering, 2025)

Tackling water contamination by oncologic drugs: Supported ionic liquids as sustainable adsorbents for cyclophosphamide removal - Rafael Francisco; Bruna Monteiro; Maria J. Santos; Francisca A. e Silva; Catia Venancio; Marcia C. Neves; Isabel Lopes; Ana C.A. Sousa; Mara G. Freire (Journal of Environmental Management, 2024)

Valorization of plant by-products in the biosynthesis of silver nanoparticles with antimicrobial and catalytic properties - Verónica Rocha; Pedro Ferreira-Santos; Cristina Aguiar; Isabel C. Neves; Teresa Tavares (Environmental Science and Pollution Research, 2024)
Biosynthesis based on natural compounds has emerged as a sustainable approach for the production of metallic nanoparticles (MNP). The main objective of this study was to biosynthesize stable and multifunctional silver nanoparticles (AgNP) using different plant by-products as reducers and capping agents. Extracts obtained from Eucalyptus globulus , Pinus pinaster, Citrus sinensis , Cedrus atlantica and Camellia sinensis by-products, were evaluated. From all plant by-products tested, aqueous extract of eucalyptus leaves (EL), green tea (GT) and black tea (BT) were selected due to their higher antioxidant phenolic content and were individually employed as reducers and capping agents to biosynthesize AgNP. The green AgNP showed zeta potential values of -31.8 to -36.3 mV, with a wide range of particle sizes (40.6 to 86.4 nm), depending on the plant extract used. Green AgNP exhibited an inhibitory effect against various pathogenic bacteria, including Gram-negative ( P. putida, E. coli , Vibrio spp. ) and Gram-positive ( B. megaterium, S. aureus, S. equisimilis ) bacteria with EL-AgNP being the nanostructure with the greatest antimicrobial action. EL-AgNP showed an excellent photodegradation of indigo carmine (IC) dye under direct sunlight, with a removal percentage of up to 100% after 75 min. A complete cost analysis revealed a competitive total cost range of 8.0–9.0 €/g for the biosynthesis of AgNP. Graphical Abstract

Environmental remediation promoted by silver nanoparticles biosynthesized by eucalyptus leaves extract - Verónica Rocha; Pedro Ferreira-Santos; Zlatina Genisheva; Eduardo Coelho; Isabel C. Neves; Teresa Tavares (Journal of Water Process Engineering, 2023)

Optimization of iron-ZIF-8 catalysts for degradation of tartrazine in water by Fenton-like reaction - Ouissal Assila; Natália Vilaça; Ana R. Bertão; António M. Fonseca; Pier Parpot; Olívia S.G. P. Soares; Manuel F.R. Pereira; Fátima Baltazar; Manuel Bañobre-López; Isabel C. Neves (Chemosphere, 2023)

Sustainable fluorescent dye-faujasite zeolite systems as tools for cancer bioimaging - Ana R. Bertão; Orhan Güney; Marta Costa; Patrícia Fontão; Olga Martinho; Susana P.G. Costa; António M. Fonseca; Olívia S.G.P. Soares; Manuel Bañobre-López; Fátima Baltazar; Isabel C. Neves (Chemical Engineering Journal, 2023)

Granulated biomass fly ash coupled with fenton process for pulp and paper wastewater treatment - João Peres Ribeiro; Nuno C. Cruz; Márcia C. Neves; Sónia M. Rodrigues; Luís A.C. Tarelho; Maria Isabel Nunes (Environmental Pollution, 2023)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

A sustained approach to environmental catalysis: Reutilization of chromium from wastewater - Bruna Silva; Isabel C. Neves; Teresa Tavares (Critical Reviews in Environmental Science and Technology, 2016)